ABOUT CREATING SOCIAL ADAPTION PREREQUISITES OF THE CHILDREN WITH DISORDERS IN DEVELOPMENT (Education in the 21st Century, 2023)
The present article reveals the challenges of creating the prerequisites for the social adaptation of children with developmental disabilities. The study of this problem is very significant, theoretically, practically and socially important, as the problems of social adaptation of children with different developmental disabilities are becoming increasingly relevant today. In particular, their social competence, which determines their employment opportunities, is essential.It is known, that the key goal and ultimate aim of the upbringing, education and development of children with disabilities is considered to be the preparation of an involved and independent member of society, capable of working and operating, to the extent possible. It is therefore practically necessary to create prerequisites for the social adaptation of children with different developmental disabilities, which define the he practical and theoretical significance of the problem under consideration, in order to solve these problems.It is understood, that developmental disabilities in children result in a breach of relations with society, community, as a source of growth, according to literature evidence and experience. These children's underdevelopment of the psyche not only leads to a decline in intellectual abilities, but also affects their adaptive capacities. We are therefore interested in how it is possible to establish prerequisites through education that lead to the social adaptation of children with developmental problems.The aim of this analysis - to disclose the key directions for creating the prerequisites for social adaptation of children with developmental disabilities - was defined by the foregoing.